Implementation of a Comparative Evaluation Method of Stable Socio-economic Development - Asan, Dosmahanbet; Batyrova, Nazygul; Aubakirova, Aktokin; Abishov, Nurjan; Kuralbayev, Almas (International Journal of Economics and Financial Issues, 2016)
The main objective of stable economic development is not only to become one of the highly developed countries, but also to create a society that provides equal rights to all people, respects freedom of each person and all kinds of his/her labor. On the various stages of society development, different economists have presented several views on this problem. Hence, the main objective of this article is to study the issue and to show modern ways of development. The following scientific and methodological conclusions are taken into consideration to determine the scientific value of the article: - Theoretical descriptions of a stable economics development concept will be updated for further improvement; - The system of financial relations development governing the activities of the local administration (region, village ) will be offered by defining stability (instability) indicators; - The offer of ways how to enhance the improvement system of stable economics service by the administration activities of Zhambul Oblast of the Republic of Kazakhstan; - The system of stable (unstable) development indicators aimed to integrate the regional development assessment to economic system by this means and the method of calculation methodology will be offered; - Variants of using stable development balance (Stable Development Balance) will be enhanced in order to succeed the productive results in integration of administrative management programs. Keywords: Stable Economics, Economic Mechanisms, Market, Human Resources, Stability and Competitiveness. JEL Classifications: C62, E21, O10, O15, R19, R58